Synthesis and solar cell application of a composite of Eu-BTB MOF with functionalized graphene. (19th September 2018) - Sharma, Sandeep Kumar; Kaur, Harmeet; Kumar, Kamal; Tyagi, Mintu; Deep, Akash
Abstract: A composite of europium-metal organic framework (Eu-BTB MOF, BTB = 1, 3, 5-tris(4-carboxyphenylbenzene) with benzoic acid functionalized graphene (BFG) has been synthesized. The successful synthesis of the Eu-BTB/BFG composite is characterized with different spectroscopic and microscopic techniques. The potential application of the above composite's thin film has been demonstrated by exploring it as a photoanode of a dye sensitized solar cell. The fabricated solar cell has delivered excellent performance in the presence of 0.5 mM MK-2 dye. The Eu-MOF/BFG composite has delivered a much better power conversion efficiency of 4.5% in comparison to a reference graphene-only cell (2.35%).